Implementation of the Education Management System at Rumah Melati Special School to Improve the Quality of Educational Personnel - Dwisa, Jowar Alyas; Permana, Hinggil; Husein, Ceceng Syarif (International Journal of Education, Information Technology, and Others, 2025)
This research aims to analyze the implementation of the education management system at the Rumah Melati Special School (SLB), especially in improving the quality of teaching staff. Rumah Melati SLB is a formal educational institution that serves children with special needs from various backgrounds. The research method used is a qualitative approach, with data collection techniques through observation, interviews and documentation. The research results show that planning, organizing, implementing and supervising educational governance are the main factors that influence improving the quality of teaching staff. Apart from that, regular training, competency development programs, and collaboration with external institutions such as the Ministry of Education and Culture and the Ministry of Health also support the successful management of education in SLB. However, challenges such as the limited number of teaching staff in line with the needs of the special education sector are still obstacles that need to be overcome. This research contributes to enriching the literature on educational management for special education institutions and provides strategic recommendations for improving the quality of inclusive education in Indonesia